Teaching and learning medical English for international medical graduates: A scoping review - Chiew Hong Ng; Yin Ling Cheung (Ibérica)
This paper reviews research on teaching and learning English for international communication in diverse contexts for international medical graduates (IMGs) using medical English as a lingua franca. Through keyword searches in Scopus and EBSCOhost research databases of English-medium peer-reviewed refereed journals from 2008 to 2022, 33 articles were selected to answer three research questions for the present study. The findings highlight the complexity, diversity and challenges of teaching and learning medical English for international communication for IMGs in terms of learners' needs and difficulties in learning medical English (e.g., low proficiency levels and issue of communicative competence), specific courses implemented for IMGs to enhance English (e.g., English for medical purposes,  English medium international project, and interdisciplinary collaboration using multimedia) and conceptual frameworks guiding teaching and learning in international multilingual environments (e.g., clinical communication skills and genre approach). Future directions in researching the teaching and learning of medical English as a lingua franca are suggested for practitioners teaching medical English for specific purposes, IMGs and prospective IMGs in international multilingual contexts and researchers specializing in interlingual medical communication.